THE SOCIO-ECONOMIC SIGNIFICANCE OF THE INTERRELATION BETWEEN AGRICULTURE AND INDUSTRY IN SURKHANDARYA REGION (FROM THE LATE 20TH CENTURY TO THE EARLY 21ST CENTURY) - Khudoyberdiev Utkir Toshmurodovich (The Conference Hub, 2025)
This study explores the socio-economic significance of the interrelation between agriculture and industry in the Surkhandarya Region from the late 20th century to the early 21st century. The research focuses on how the integration of agricultural production and industrial processing has contributed to regional economic development, employment, and rural modernization. It examines the transformation of the agrarian structure, the establishment of agro-industrial complexes, and their role in improving living standards. Using historical and statistical analysis, the study identifies key trends in industrialization that have strengthened agricultural productivity and export potential. Particular attention is given to the impact of state policies, private investment, and technological innovation on the agro-industrial sector. The results show that the synergy between agriculture and industry has been a driving force for balanced regional growth. The study concludes that sustainable cooperation between these sectors is essential for ensuring food security, economic diversification, and long-term development in Surkhandarya Region.
Keywords: Surkhandarya Region; industrial enterprises; socio-economic development; modernization; employment; regional economy; sustainable growth.